KEYNOTE-022 part 3: a randomized, double-blind, phase 2 study of pembrolizumab, dabrafenib, and trametinib in BRAF-mutant melanoma. Issue 2 (24th December 2020) - Ferrucci, Pier Francesco; Di Giacomo, Anna Maria; Del Vecchio, Michele; Atkinson, Victoria; Schmidt, Henrik; Schachter, Jacob; Queirolo, Paola; Long, Georgina V; Stephens, Rosalie; Svane, Inge Marie; Lotem, Michal; Abu-Amna, Mahmoud; et al.
Abstract : Background: In the KEYNOTE-022 study, pembrolizumab with dabrafenib and trametinib (triplet) improved progression-free survival (PFS) versus placebo with dabrafenib and trametinib (doublet) without reaching statistical significance. Mature results on PFS, duration of response (DOR), and overall survival (OS) are reported. Methods: The double-blind, phase 2 part of KEYNOTE-022 enrolled patients with previously untreated BRAF V600E/K -mutated advanced melanoma from 22 sites in seven countries. Patients were randomly assigned 1:1 to intravenous pembrolizumab (200 mg every 3 weeks) or placebo plus dabrafenib (150 mg orally two times per day) and trametinib (2 mg orally one time a day). Primary endpoint was PFS. Secondary endpoints were objective response rate, DOR, and OS. Efficacy was assessed in the intention-to-treat population, and safety was assessed in all patients who received at least one dose of study drug. This analysis was not specified in the protocol. Results: Between November 30, 2015 and April 24, 2017, 120 patients were randomly assigned to triplet (n=60) or doublet (n=60) therapy. With 36.6 months of follow-up, median PFS was 16.9 months (95% CI 11.3 to 27.9) with triplet and 10.7 months (95% CI 7.2 to 16.8) with doublet (HR 0.53; 95% CI 0.34 to 0.83). With triplet and doublet, respectively, PFS at 24 months was 41.0% (95% CI 27.4% to 54.2%) and 16.3% (95% CI 8.1% to 27.1%); median DOR was 25.1 months (95% CI 14.1 to not reached) and 12.1 months (95% CI 6.0 to 15.7), respectively. Median OS was not reached with triplet and was 26.3 months with doublet (HR 0.64; 95% CI 0.38 to 1.06). With triplet and doublet, respectively, OS at 24 months was 63.0% (95% CI 49.4% to 73.9%) and 51.7% (95% CI 38.4% to 63.4%). Grade 3–5 treatment-related adverse events (TRAEs) occurred in 35 patients (58%, including one death) receiving triplet and 15 patients (25%) receiving doublet. Conclusion: In BRAF V600E/K -mutant advanced melanoma, pembrolizumab plus dabrafenib and trametinib substantially improved PFS, DOR, and OS with a higher incidence of TRAEs. Interpretation of these results is limited by the post hoc nature of the analysis.